A Brief Discussion of Changing Temperament Which is the Core of Zhang Bingzhi’s Cultivation Theory and Efforts - Yang, Rui; Chen, Wenyi; Cao, Wenya (Journal of Educational Research and Policies, 2025)
Zhang Bingzhi, as a Qing Dynasty scholar of science, emphasized work in his thought and presented a distinctive color of science. In Zhang Bingzhi’s rationalist thought, the concept of “rationality and qi” provides a metaphysical basis for human nature and destiny, and provides a basic explanation for the principle of the development of the world’s movement. “The theory of cultivations and efforts, on the other hand, takes the “theory of qi” as its foundation, the “theory of heart” as its basis, and the “theory of destiny” as its guide. It explores how to realize the Divine Principle and how to “know one’s destiny as the beginning” and then “attain one’s destiny” in the process of the operation of reason and mind. Zhang Bingzhi’s theory of cultivations and efforts is centered on “changing temperaments”; he regards “changing temperaments” as the means and goal of scholars’ cultivation efforts, and regards “setting ambitions” as a means of “changing temperaments” and a goal of scholars’ cultivation efforts. He regarded “changing temperament” as the means and goal of scholars’ cultivation efforts, and regarded “establishing the will” as the starting point of “changing temperament” and “single-minded conviction” and “cultivation of mind” as the guarantee of “changing temperament”. His emphasis on “changing temperament” established the basic tendency of “work” as the main focus of his scientific thought, and revealed the basic theoretical characteristics of his emphasis on work in the already developed.